Animal production in a Crop-Livestock-Forest integration system ILPF as a strategy for mitigating climate change - Martinez, Flavia Rodrigues; Almeida, Fabiano Martins de; Duarte, Júlia Paschoareli Ferro; Souza, Kátia Lirian Rocha; Azevedo, Caroline Gomes; Filho, Cecílio Viega Soares (Seven Editora, 2023)
With the increase in demand for food, agricultural activity began to be characterized by standardized monoculture systems and began to be carried out in an intensified manner, however, due to the high demand for natural resources, it has been presenting itself with low environmental sustainability. DOI:https://doi.org/10.56238/alookdevelopv1-160